Analisis Muatan Nature of Science (NOS) pada Buku Teks Kimia SMA di Kota Bandung - Annisa Mustika Pertiwi, - (2020)
It is stated that the lack of scientific literacy is influenced by lack understanding of NOS. This can be caused by the lack aspects of NOS in textbooks as its one of the main learning resources of students. Therefore, this study aims to obtain information related to Nature of Science (NOS) in the most dominant chemistry textbooks used by teachers and 10th grade high school students in Bandung. The method used in this research is quantitatively descriptive using a protocol developed by Lee (2007) to obtain the percentage of each aspect that contains NOS and content analysis qualitatively to obtain an overview of the presentation of NOS in the high school chemistry textbooks analyzed. The results showed that the textbook contained 76% of science as a body knowledge, 13% of science as a way of investigation, 8% of science as a way of thinking and 3% of interaction between science, technology and society. It is proved that the chemistry textbook has not shown the balance of every aspect of NOS.